Building a financially literate Philippines a study on the determinants of financial literacy among Filipino adults - Batara, Joan Marie; Formoso, Nicole Danielle T.; Alburo, Florian A. (Quezon City School of Economics, University of the Philippines Diliman, 2021)
Literacy has grown from a term that defines the ability of reading and writing to concepts that describe “new literacies” specific to subject areas and skills, one of which is financial literacy. Although the body of literature on financial literacy and its determinants has continuously been growing, spanning different focus areas and countries, there is much room for investigation in the Philippine setting. Most research on the determinants of Filipinos’ financial literacy has focused on specific target groups like teachers and university students. Using data from the Financial Inclusion Survey (FIS) 2019 of Bangko Sentral ng Pilipinas with a sample size of 1,200 Filipino adults, this paper conducts a study on the determinants of financial literacy in the Philippines. Ordinal logistic regression models were used to determine the effects of these factors on financial literacy which was measured by the score of each respondent on the financial literacy questions of the FIS 2019 survey. The results show that all
the demographic and socioeconomic variables studied had no significant effect on financial literacy. Meanwhile, all geographic factors namely being of urban residence and residing outside of Metro Manila had negative effects on financial literacy. For financial inclusion variables, only account holding and investment holding show positive effects while both insurance holding and having formal credit are both statistically insignificant. The presence of significance for some variables confirms ideas posited by the Social Learning Theory, the Consumer Socialization Theory, and the concept of Financial Socialization. The findings also confirm an insight from related literature which is that most variables studied in this area of research often affect financial literacy in developed economies more than developing economies such as the Philippines.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Financial literacy -- Economic conditions -- Philippines